2010
DOI: 10.1542/peds.2010-1596
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Nurse Practitioners: Distribution, Roles and Scope of Practice

Abstract: As with many health care professionals, the supply of NNPs may not be distributed according to need. With increasing concern regarding the availability of NNPs, comprehensive studies that examine the demand for NNPs and the roles of other clinicians in the NICU should provide a greater understanding of appropriate NICU workforce capacity and needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…This is despite a strong job market, planned increases in hiring NNPs, and a seemingly growing shortage of NNPs (Cusson et al, 2008;Freed et al, 2012;Honeyfield, 2009). Further, of those programs remaining open, only one third filled all available slots for the entering class of 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is despite a strong job market, planned increases in hiring NNPs, and a seemingly growing shortage of NNPs (Cusson et al, 2008;Freed et al, 2012;Honeyfield, 2009). Further, of those programs remaining open, only one third filled all available slots for the entering class of 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, NPs who provide specialized care to neonates and children have not experienced increases in their pipeline at all (Freed, Dunham, Loveland-Cherry, et al, 2010). This has resulted in shortages of NPs educated to provide care to these populations without deliberate efforts to address the problem (Cusson et al, 2008;Freed, Dunham, Loveland-Cherry, et al, 2010;Honeyfield, 2009). Recent reports have highlighted both the current shortage of neonatal nurse practitioners (NNPs) and the intentions of hospital CEOs to hire additional NNPs in the coming 3-5 years (Bellini, 2013;Cusson et al, 2008;Freed, Dunham, Lamarand, Loveland-Cherry, & Martyn, 2010;Freed, Dunham, Moran, & Spera, 2012;Honeyfield, 2009;National Association of Neonatal Nurses, 2013).…”
mentioning
confidence: 99%
“…The shortage of ANNPs is also a problem in the UK,9 and although faculty shortages are an issue, this is partly offset by the role of consultant neonatologists in delivering the ANNP programs. This makes sense, as even in the USA, most ANNPs work under the supervision of consultant neonatologists 21. The LJMU MSc program has taken this one step further and integrated the ANNP program’s neonatal modules with the postgraduate medical-education program for neonatology.…”
Section: Shortage Of Anps and Educatorsmentioning
confidence: 99%
“…Although most provide clinical expertise in the intensive care environment, UK ANNPs have developed other models of care, including local lead practitioners in small stand-alone units24 or practitioner-led transport and retrieval services 25. A small number of ANNPs in the USA have developed a community-based role outside the intensive care environment 21. This process of evolution requires programs that are adaptable; this flexibility is facilitated by a modular curricula structure, with modules common to several training pathways.…”
Section: The Anp Rolementioning
confidence: 99%
“…1,2 Additionally, growing reliance on mid-level providers in the neonatal intensive care unit (NICU) limit resident opportunities to perform procedures, including endotracheal intubation-which remains an important milestone for graduation. [11][12][13][14][15] One study demonstrated that pediatric residents were the first to attempt a procedure in the NICU less than one-third of the time. 15 Thus, incoming NPM fellows are at risk for graduating without the necessary knowledge base and experience to successfully transition to postgraduate training.…”
mentioning
confidence: 99%